Development of three-dimensional (3D) grayscale Photolithography process for microfluidic curvature Structures - Abdul Hamid, Intan Sue Liana (2018)
Three-dimensional (3D) microstructures can enhance the optical, electrical and mechanical properties of the microfluidic system. However, the 3D microfabrication is challenging when simultaneous control over fabrication of lateral and vertical dimensions is required. To achieve such control, grayscale photolithography technique has been comprehensively studied as an alternative to the current 3D microfabrication technique. Current techniques require highly sophisticated and PTTA expensive equipments, with slow point-to-point or layer-by-layer approach of pattern exposure. The proposed grayscale photolithography technique in this research has been used in realization of microstructures with height between 163.8 µm and 1108.7 µm in a single exposure through grayscale photomask. The grayscale photolithography technique developed in this study has been applied for realization of 3D microstructures in fiber optic-based refractive index sensor, PDMS surface wettability modification and passive micromixers. The fabrication of fiber optic- based refractive index sensor has been improved by providing a 3D microfluidic environment to help float the fiber optic inside the microchannel. High sensitivity of 1509.3 nm/RIU was achieved for refractive index sensing of different Sodium Chloride solution concentrations. Fabrication of micro curvature structures on PDMS surface has increase its wettability into superhydrophobic state with water contact angle 157.3 °. Various shapes and designs of micromixers, including the different height of obstacles inside the microchannel have been fabricated and achieve a good mixing performance. In sum, a 3D microfabrication by grayscale photolithography technique has been developed, with functional applicability for fabrication of several microfluidic functions.